Uterine Horn Intussusception in a Chihuahua Bitch - Samaneh Ghasemi; Mohamad Reza Emami; Ali Mirshahi; Pouria Khanzadeh; Sina Yal Beyranvand; Mohammad Mahdi Zarezadeh (The Iranian Journal of Veterinary Science and Technology, 2023)
Uterine horn intussusception has rarely been reported in bitches. However, the pathogenesis is not entirely clear and the incidence of uterine intussusception in bitches is unknown. This disorder occurs during the postpartum period and is a challenging clinical condition in terms of presentation, diagnosis, and management. In this report, a case of uterine horn intussusception is described in a four-year-old female Chihuahua bitch, which presented with abdominal pain, lethargy, anorexia, tremors, recumbency, and ongoing reddish vaginal discharge 20 days after whelping two pups. All the hematological and biochemical test results were within normal ranges except for a decreased calcium level. Ultrasonographic examination revealed the multilayered appearance of the uterine wall. The midline laparotomy confirmed the invagination of a proximal segment of the uterine horn into its distal segment near the uterine body. Ovariohysterectomy was performed as the recommended treatment. This case highlights the importance of assessing abdominal pain to avoid delay in diagnosis and management. Moreover, uterine intussusception should be considered as a differential diagnosis in bitches with the symptoms of abdominal pain during the postpartum period.